2012
DOI: 10.1038/bjc.2012.69
|View full text |Cite
|
Sign up to set email alerts
|

Repeated transarterial chemoembolisation using different chemotherapeutic drug combinations followed by MR-guided laser-induced thermotherapy in patients with liver metastases of colorectal carcinoma

Abstract: Background:To evaluate a treatment protocol with repeated transarterial-chemoembolisation (TACE) downsizing before MR-guided laser-induced interstitial thermotherapy (LITT) using different chemotherapeutic combinations in patients with unresectable colorectal cancer (CRC) liver metastases.Methods:Two hundred and twenty-four patients were included in the current study. Transarterial-chemoembolisation (mean 3.4 sessions per patient) was performed as a downsizing treatment to meet the LITT requirements (number⩽5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…Descriptively, four Y-90 studies, 19,22,23,26 reported on 12-29% of patients experiencing severe to life-threatening adverse events (Grade 3-4), compared to 3-10% of patients in two DEB-TACE studies, 28,29 and 0.4% in one cTACE study. 30 Instances of 30-day mortality and/or procedure-related mortality were rare across all studies, occurring in one, two and three patients in cTACE, DEB-TACE and Y-90 studies, respectively.…”
Section: Safety and Toxicitymentioning
confidence: 92%
“…Descriptively, four Y-90 studies, 19,22,23,26 reported on 12-29% of patients experiencing severe to life-threatening adverse events (Grade 3-4), compared to 3-10% of patients in two DEB-TACE studies, 28,29 and 0.4% in one cTACE study. 30 Instances of 30-day mortality and/or procedure-related mortality were rare across all studies, occurring in one, two and three patients in cTACE, DEB-TACE and Y-90 studies, respectively.…”
Section: Safety and Toxicitymentioning
confidence: 92%
“…8 During TACE, a catheter is introduced into the femoral artery using the Seldinger technique. 11 Using the femoral approach, a catheter is passed through the coeliacal trunk into the main hepatic artery and then into the relevant branch that is providing the tumours with blood flow. Angiography is used to confirm the correct position of the tip of the catheter and to detect any anatomical abnormalities which may require repositioning of the catheter to avoid inadvertant complications resulting from the pharmaceutical agents being delivered to incorrect anatomical sites and structures.…”
Section: Current Trends In Interventional Treatment Of Colorectal Canmentioning
confidence: 99%
“…37,38 The combination of TACE and LITT could help to enlarge the group of patients on whom an effective therapy could be offered. They showed no prognostic influence in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%